Surviving complete gastric infarction in remote Australia. Issue 5 (9th May 2019) - Gray, Andrew; Lewis, David
Abstract: Gastric volvulus is a potentially lethal condition with mortality rates reported up to 50%. The high mortality rate is largely due to the rarer complication of gastric infarction, the diagnosis of which is often difficult. From the small series published, it is known that delays to receiving definitive surgical intervention negatively impacts patient outcomes. We present a case of long-term survival of a 69-year-old man who presented to his local hospital in remote Australia with gastric volvulus and complete gastric infarction. His initial management was delayed as he could not undergo life-saving surgery at his presenting hospital. He was transferred to the regional referral hospital and survived both an upfront damage-control oesophagogastrectomy and then transfer to a metropolitan centre for alimentary tract reconstruction. He was alive and living at home without major postoperative morbidity 12 months later.